1995
DOI: 10.1074/jbc.270.51.30290
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the μ3 Opiate Receptor in Endothelial Cells

Abstract: Initial confinement of opiate receptors to the nervous system has recently been broadened to several other cell types. Based on the well established hypotensive effect of morphine, we hypothesized that endothelial cells may represent a target for this opiate substance. Endothelial cells (human arterial and rat microvascular) contain a high affinity, saturable opiate binding site presumed to mediate the morphine effects that is stereoselectively and characteristically antagonized by naloxone. This opiate alkalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(30 citation statements)
references
References 25 publications
1
27
0
2
Order By: Relevance
“…The inhibition of cell spreading (26 -28) is in agreement with observations made in the present study, namely, that anandamide receptor coupling to NO may be the mechanism initiating this cell rounding (6,29). 2 Given the fact that naloxone does not antagonize or bind to the anandamide receptor, these signal systems appear to be distinct.…”
Section: Figsupporting
confidence: 81%
See 1 more Smart Citation
“…The inhibition of cell spreading (26 -28) is in agreement with observations made in the present study, namely, that anandamide receptor coupling to NO may be the mechanism initiating this cell rounding (6,29). 2 Given the fact that naloxone does not antagonize or bind to the anandamide receptor, these signal systems appear to be distinct.…”
Section: Figsupporting
confidence: 81%
“…Tip diameter of the probe (25 m) permitted the use of a micromanipulator (Zeiss-Eppendorff) attached to the stage of an inverted microscope (Nikon Diaphot) to position the sensor 10 m above the cell surface. Calibration of the electrochemical sensor was performed by the use of different concentrations of nitrosothiol donor S-nitroso-N-acetyl-DL-penicillamine, as previously detailed (6).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that opioids also induce nitric oxide synthase (NOS), hemoxygenase-1 (HO-1) and cyclooxygenase-2 (COX-2) [17,18,19] which are potent vasodilators. Further, we found that morphine promotes cell proliferation and survival in a manner similar to the effects of vascular endothelial growth factor (VEGF) on endothelial cells [18, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the participation of a synthetic analog of [Met]enkephalin ([D-Ala2,Met5] enkephalinamide, DAMA) in immunoregulatory activities, especially cellular adherence and migration, has been obtained in the mollusc Mytilus edulis [30]. The specific function for [Met]enkephalin in immunoregulation, mediated perhaps by a special subtype of delta receptor [31,32]. LPS and opioids can activate distinct populations of Mytilus immunocytes, and distinct immunoactive cell populations seem to exist since apparently different subsets of cells react when exposed to LPS or opioids and the opioid antagonist naloxone [33].…”
Section: Innate Immune Response Mediated By Opioid Peptidesmentioning
confidence: 99%